An innovative approach to prioritizing soil conservation areas under diverse scenarios by leveraging the complementary roles of soil retention services and soil erosion indicators - Eshetu Shifaw; Jinming Sha; Xiaomei Li; Peng Zhao; Jianwan Ji; Hao Zhang; Ashenafi Yimam Kassaye; Shuhui Lai; Zhonglin Ji; Yusheng Yang (Journal of Hydrology: Regional Studies)
Study region: Upper Blue Nile Basin, the largest in Ethiopia in terms of annual water runoff and soil loss. Study focus: A new framework for identifying soil conservation priority areas has been proposed. Existing methods often focus solely on soil loss, neglecting soil conservation indicators. Few studies consider multiple scenarios. The Sediment Delivery Ratio model was used to estimate soil conservation services (Avoided Erosion, AE; Sediment Trapping, ST) and soil erosion (Soil Loss, SL; Sediment Export, SE). These indicators were integrated using the Ordered Weighted Averaging method. New hydrological insights for the region: The results revealed an initial decline in all indicators (2000–2010), followed by an increase (2010–2020). The total values of AE, ST, SL, and SE ranged from 11.98 to 12.49 billion, 2.07–2.15 billion, 660.41–684.06 million, and 102.35–105.75 million tons/year, respectively. Factors such as rainfall, slope, and soil types caused non-linear effects of land cover change. The study proposes conservation priority areas under 11 scenarios, offering a range of decision-making options. Among these, the 7th is recommended as the most optimal, balancing conservation efficiency, moderate trade-offs, and planners' optimism. Implementing conservation measures in high and very high priority classes under this scenario can retain 2097.03 t/ha/yr of soil and reduce sediment export by 20.03 t/ha/yr. This advanced conservation prioritization framework can be replicated in regions beyond the UBNB.